True believers - Haddam, Jane, 1951-2019- (Haddam, Jane, 1951-2019- Gregor Demarkian books, 2001)
Early One Morning at St. Anselm's Church in Philadelphia, a parishioner sneaks the body of his wife into the sacristy and then commits suicide. The husband, known to be devoted to his wife, is presumed to have killed himself out of grief. His wife, a severe diabetic, is assumed to have died of natural causes - until the coroner discovers that she actually died of arsenic poisoning. The police close the murder case, believing that the husband was clearly responsible, but one of the nuns at St. Anselm's doesn't accept the prevailing wisdom. Sure that the husband is innocent, she asks Gregor Demarkian, the retired head of the FBI's Behaviorial Science Unit, to investigate. With tensions mounting among the city's religious groups, agitated by outside extremists, Demarkian's investigation is made difficult by the environment. Bennis Hannaford, an acclaimed author and Demarkian's lover, is undergoing a crisis of her own while the many and various denizens of Cavanaugh Street - their Armenian-American neighborhood - are involved in various uproars themselves. But at the base of everything is a mysteriously murdered young woman and the most perplexing case yet for Gregor Demarkian.